TRACE AND RARE EARTH ELEMENT GEOCHEMISTRY OF PHOSPHATE NODULES FROM THE LOWER CAMBRIAN BLACK SHALE SEQUENCE IN THE MUFU MOUNTAIN OF NANJING, JIANGSU PROVINCE, CHINA - Jiang S.-Y.; Zhao H.-X.; Yang T.; Yang J.-H.; Ling H.-F.; Chen Y.-Q. (My University, 2007)
Phosphate nodules are abundant in the lowermost section of the Lower Cambrian black shale sequence along a NE-trend belt in the Yangtze Platform, south China. In this study, we examined the Neoproterozoic-Cambrian Mufu Mountain section near Nanjing of Jiangsu province, and conducted a detailed trace and rare earth element (REE) study on the phosphate nodules. We employed a step-leaching acid dissolution protocol of 1 M HAc and 1 M HCl, respectively, to separate carbonate from phosphate mineral contributions in the nodules. Both the HAc-leached and HCl-leached fractions of the phosphate nodules show similar symmetrical variations in trace and REE concentrations and ratios. The total REEs and a number of redox-sensitive trace metals such as V, Cr, Mo, Ni abundances show a systematic increase from the core to rim, whereas the U and Mn abundances decrease from the core to rim in most of the nodules. Similar trends are also observed for the Rb/Sr, U/Th, Co/Ni, and V/Ni ratios, but these trends in the HAc-leached fractions are less pronounced than the HCl-leached fractions. All of the HCl-leached fractions for the nodule cores show seawater-like shale-normalized REE patterns, but the rims of the nodules display slightly MREE-enriched and HREE-depleted patterns. We suggest that the phosphate nodules may have formed in a basinal setting beneath a stratified water column during Early Cambrian, and the compositional variations of REEs and redox-sensitive trace elements from the core to rim may record a changing redox condition and fluid mixing during different stages of nodule growth. The cores of the nodules preserve more pronounced negative Ce anomalies and progressively HREE-enriched patterns, which may retain primary Early Cambrian seawater chemistry, whereas the nodule rims record chemistry consistent with changed redox conditions and/or influences from pore fluids such as generated from degradation of organic matter. © 2007.
Keywords: BLACK SHALE; LOWER CAMBRIAN, SOUTH CHINA; PHOSPHATE NODULE; RARE EARTH ELEMENTS; REDOX-SENSITIVE TRACE ELEMENTS; Cambrian; Neoproterozoic; Paleozoic::Cambrian; Палеозой::Кембрийская; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская